An elite hockey player`s experiences of video-based coaching: A poststructuralist reading - Taylor, W. G.; Potrac, P.; Nelson, L. J.; Groom, R. (International Review for the Sociology of Sport, 2017)
In this article, we present a poststructuralist reading of Claire`s (a pseudonym) experiences of receiving video-based coaching in elite level field hockey. Data were gathered through a series of in-depth interviews that formed part of a recursive and iterative data collection and analysis process. Interpreting Claire`s stories through a neo-Foucauldian application of Mathiesen`s synopticon revealed how the presence of a video camera mediated Claire`s practice and imposed a critical gaze, one that became collectively and institutionally consumed. We argue that the thoughts presented in this paper have significant implications for coach practice and education and that, as a result, there is a need for further critical inquiry into coaches` uses of video-based technology.